ANALYSIS OF PERCEPTION AND ATTITUDE OF LOCAL GOVERNMENT OF EAST LAMPUNG REGENCY TO WEBSITE AS A REPRESENTATION OF GOOD GOVERNACE - Meilin Malita Ridhatika (Metakom, 2018)
The ease and usefulness of technology can be a factor supporting the use of the website as a medium in providing information and public services in order to realize good governance. The purpose of this research is to know perception and attitude of local government apparatus of East Lampung Regency to website as representation of good governance. The theory used was Technology Acceptance Model (TAM) by Davis (1989). Technique of research analysis is descriptive statistic. Sample amounted to 57 respondents from population amounted to 133 employees in the Regional Secretariat of East Lampung Regency. Perception was measured by dimensions of perceived of usefullness, ease of use and interest in using website. Attitude was measured by dimensions of cognitive, affectice and conative. The result showed that perception of government appratus of East Lampung Regency consider that website functionally gives ease and benefit to increase performance in giving information and public service. Nevertheless, in attitude side, government apparatus do not yet reach stage of website in giving information and public service. Keywords : perception, attitude, Tecnology Acceptance Model, government employee of East Lampung Regency